2022
DOI: 10.3390/ijerph19020920
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Assessment to Radiofrequency Electromagnetic Fields in Occupational Military Scenarios: A Review

Abstract: (1) Background: Radiofrequency radiations are used in most devices in current use and, consequently, the assessment of the human exposure to the radiofrequency radiations has become an issue of strong interest. Even if in the military field there is wide use of radiofrequency devices, a clear picture on the exposure assessment to the electromagnetic field of the human beings in the military scenario is still missing. (2) Methods: a review of the scientific literature regarding the assessment of the exposure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
1
1
0
1
Order By: Relevance
“…The results showed that placing the operator’s arm on the vehicle increased the SAR from 0.43 to 2.03 mW kg \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} $^{-1}$\end{document} . However, the human body exposure in this study was in line with guideline limits of military applications ( 17 ) .…”
Section: Detailed Review and Analysissupporting
confidence: 71%
See 1 more Smart Citation
“…The results showed that placing the operator’s arm on the vehicle increased the SAR from 0.43 to 2.03 mW kg \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} $^{-1}$\end{document} . However, the human body exposure in this study was in line with guideline limits of military applications ( 17 ) .…”
Section: Detailed Review and Analysissupporting
confidence: 71%
“…reviewed studies related to RF-EMF exposure in occupational military scenarios. They found that exposure varied depending on the source of RF-EMF exposure, and further studies are necessary to assess exposure for specific devices and technologies such as 5G devices, especially in military scenarios ( 17 ) . In recent years, there has been a surge of interest in computational dosimetric studies on RF-EMF exposure above 6 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…Como os RPAS não dependem de pilotos de voo, eles inicialmente buscaram atender aos requisitos militares de armas e inteligência (Yaacoub et al, 2020;Abade et al, 2016). Os dispositivos RPAS modernos são controlados remotamente ou operam de forma autônoma com software sincronizado com GPS e outros sensores, pelos quais suas rotas e funções são predefinidas (Gallucci et al, 2022;Baena et al, 2018).…”
Section: Detecção Reconhecimento E Contagem De Animais Com Imagens De...unclassified